Penggunaan Bahasa Indonesia Baku dalam Proses Pembelajaran antara Dosen dan Mahasiswa - Wahyuni Shofinna Nur (STIKes Ibnu Sina Ajibarang, 2025)
The use of standard Indonesian is one of the key aspects of the learning process, particularly in higher education settings, which involve interactions between lecturers and students. This article aims to examine the extent to which standard Indonesian is applied in academic communication during the learning process. This study employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and document analysis. The findings reveal that the application of standard Indonesian by lecturers and students still faces several challenges, such as a lack of awareness about the importance of using standard language and the influence of informal or regional languages. However, the study also highlights that consistent use of standard Indonesian can enhance communication effectiveness, clarify the delivery of materials, and foster a more professional learning atmosphere. The article recommends training and socialization efforts on the use of standard Indonesian for lecturers and students to improve the quality of academic communication in higher education.